PSXIV-3 Humoral immune responses in ostrich chicks to dietary L-carnitine supplementation. (7th December 2018) - Hajibabaei, A; Casey, N
Abstract: Ostriches are susceptible to Newcastle disease virus (NDV); farmed ostriches are inoculated against the infection. The research aimed to establish humoral responses of ostrich chicks to L-carnitine to improve immunity against NDV. A dietary supplement of L-carnitine was administered to chicks from day-old to 81 days; sera antibody titre was the humoral immune response indicator. Thirty-two day-old Black Neck chicks were randomly divided into four treatments with four replicates of two chicks each. A basal diet was fed supplemented with L-carnitine at concentrations of 0 (T0 ), 125 (T125 ), 250 (T250 ) or 600 (T600 ) mg/kg. Primary inoculation with an inactive vaccine was at Day 30 and a booster at Day 51. Blood was sampled at Days 30, 51, 70 and 81. Monitoring was over three phases: 1: 20 days after the primary immunisation; 2: 20 days and 3: 31 days after the booster. A commercially available chicken anti-NDV enzyme-linked immunosorbent assay was modified for the detection of anti-NDV. Results: Treatments and time periods influenced responses (P<0.01) with interactions occurring between treatments and time periods (P<0.05); T125 and T250 had highest responses (P<0.05) over the total period; differences betweens T0 and T600 and between T125 and T250 were NS (P>0.05); Days 70 and 81 had higher responses than Day 50 (P<0.05), and Day 70, the highest. The results suggest that L-carnitine supplementation at levels of 125 and 250 mg/kg have positive effects on antibody production and immune responses in Black Neck ostrich chicks against NDV.